CYT387 restores Th17/Treg cell balance and inhibits mature osteoclast cell formation by regulating SOX-5 signaling in rheumatoid arthritis - Susmita Srivastava; Mahaboobkhan Rasool (Bangladesh Pharmacological Society, 2023)
The present study was conducted to investigate the therapeutic efficacy of CYT387 in rheumatoid arthritis pathogenesis concerning T helper 17 cell/regulatory T cell (Th17/Treg) imbalance and osteoclastogenesis. In this study, CYT 387 inhibited the proliferation of Th17 cells and collectively relocated FoxP3 + Treg cell differentiation in vitro. CYT387 mitigated the secretion of pathogenic IL-17 via reduced ROR-γt expression and restored the elevated expression of IL-10 by increasing FOXP3 activity. Alternatively, CYT387 abrogated RANKL expression and significantly increased osteoprotegerin levels by reducing SOX-5 activity. Furthermore, in a co-culture system of IL-6 and sIL-6R stimulated adjuvant-induced arthritic fibroblast-like synoviocytes and monocytes/macrophages collected from rat bone marrow, CYT387 reduced osteoclast formation and bone resorptive activity. In conclusion, CYT387 modulated IL-6/sIL-6R dependent JAK1/STAT3 activation and signaling mechanisms in CD4+T cells under Th17 differentiation conditions and osteoclast cells via dampened activation of SOX-5.